2017
DOI: 10.1002/2016gb005488
|View full text |Cite
|
Sign up to set email alerts
|

Biological production, export efficiency, and phytoplankton communities across 8000 km of the South Atlantic

Abstract: In situ oxygen tracers (triple oxygen isotope and oxygen/argon ratios) were used to evaluate meridional trends in surface biological production and export efficiency across~8000 km of the tropical and subtropical South Atlantic in March-May 2013. We used observations of picophytoplankton, nanophytoplankton, and microphytoplankton to evaluate community structure and diversity and assessed the relationships of these characteristics with production, export efficiency, and particulate organic carbon (POC) fluxes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 220 publications
(284 reference statements)
0
8
0
Order By: Relevance
“…Our cruise track spanned a broad segment of the western Atlantic Ocean and included samples from the surface ocean down to just above the seafloor. There were no significant differences in the flux of particulate organic carbon, measured at 125 m, along this transect (Durkin et al ), and net community production and gross primary production were relatively uniform (Howard et al ). We measured the concentrations of TOC and TON in our samples using well‐established protocols.…”
Section: Discussionmentioning
confidence: 90%
“…Our cruise track spanned a broad segment of the western Atlantic Ocean and included samples from the surface ocean down to just above the seafloor. There were no significant differences in the flux of particulate organic carbon, measured at 125 m, along this transect (Durkin et al ), and net community production and gross primary production were relatively uniform (Howard et al ). We measured the concentrations of TOC and TON in our samples using well‐established protocols.…”
Section: Discussionmentioning
confidence: 90%
“…Prochlorococcus was numerically more abundant in the surface waters of the south and equatorial Atlantic than Synechococcus, picoeukaryotes, and nanoeukaryotes (Howard et al 2017). In the southern and equatorial Atlantic, phytoplankton data were complemented by the prokaryotic community composition based on 16S rRNA gene sequences (Figure S4).…”
Section: Microbial Taxa Abundancementioning
confidence: 95%
“…In recent years, it is observed that the mixed layer has a component of 17 O-enriched O 2 accumulated in the less vented thermocline by either entrainment of water or vertical turbulent flux from the thermocline, which results in an overestimation of mixed layer GOP. Wurgaft et al added a term for GOP contribution from beneath the mixed layer to a simplified form of eq . Haskell et al divided the euphotic regions into the mixed layer and below mixed layer (BML) and constructed similar equations with GOP of the mixed layer influenced by the BML, and GOP of BML influenced by the deep water column below the euphotic depth.…”
Section: Applicationsmentioning
confidence: 99%